Determinants of the exclusive breastfeeding abandonment: psychosocial factors - Mariana Campos Martins Machado; Karine Franklin Assis; Fabiana de Cássia Carvalho Oliveira; Andréia Queiroz Ribeiro; Raquel Maria Amaral Araújo; Alexandre Faisal Cury; Silvia Eloiza Priore; Sylvia do Carmo Castro Franceschini (Universidade de São Paulo, 2014)
OBJECTIVE To assess the determinants of exclusive breastfeeding abandonment. METHODS Longitudinal study based on a birth cohort in Viçosa, MG, Southeastern Brazil. In 2011/2012, 168 new mothers accessing the public health network were followed. Three interviews, at 30, 60, and 120 days postpartum, with the new mothers were conducted. Exclusive breastfeeding abandonment was analyzed in the first, second, and fourth months after childbirth. The Edinburgh Postnatal Depression Scale was applied to identify depressive symptoms in the first and second meetings, with a score of ≥ 12 considered as the cutoff point. Socioeconomic, demographic, and obstetric variables were investigated, along with emotional conditions and the new mothers' social network during pregnancy and the postpartum period. RESULTS The prevalence of exclusive breastfeeding abandonment at 30, 60, and 120 days postpartum was 53.6% (n = 90), 47.6% (n = 80), and 69.6% (n = 117), respectively, and its incidence in the fourth month compared with the first was 48.7%. Depressive symptoms and traumatic delivery were associated with exclusive breastfeeding abandonment in the second month after childbirth. In the fourth month, the following variables were significant: lower maternal education levels, lack of homeownership, returning to work, not receiving guidance on breastfeeding in the postpartum period, mother's negative reaction to the news of pregnancy, and not receiving assistance from their partners for infant care. CONCLUSIONS Psychosocial and sociodemographic factors were strong predictors of early exclusive breastfeeding abandonment. Therefore, it is necessary to identify and provide early treatment to nursing mothers with depressive symptoms, decreasing the associated morbidity and promoting greater duration of exclusive breastfeeding. Support from health professionals, as well as that received at home and at work, can assist in this process.